'StoSS in [die] Modellschweiz ein': Simulating Switzerland as Alpine Heimat in Stefan Kaegi's Mnemopark (2005). (25th October 2018) - McClelland, Richard
Abstract: In his postdramatic theatre production Mnemopark (Theater Basel, 2005), Swiss director Stefan Kaegi presents a miniaturized vision of Switzerland on the stage in the form of a model railway. Drawing on the wider dramaturgical techniques of Kaegi's theatrical practices with the award-winning German-Swiss collective Rimini Protokoll, throughout the production five 'Experts of the Everyday' layer their memories and experiences of reality onto the concrete space of the model to produce a simulated vision of Switzerland as Heimat on the stage. In applying Jean Baudrillard's theory of simulation to Mnemopark, this article addresses the disconnect engendered between the model and the extra-theatrical reality that it supposedly represents by focusing on how the production juxtaposes multiple traces of reality on the stage. Thus, I highlight how Mnemopark interrogates contemporary understandings of Switzerland as Heimat in a way that posits a future reconceptualization of the nation that is inclusive and potentially utopian.